TINJAUAN KAPABILITAS APARAT PENGAWASAN INTERNAL PEMERINTAH BERDASARKAN INTERNAL AUDIT CAPABILITY MODEL UNTUK MEWUJUDKAN PERAN YANG EFEKTIF DI INSPEKTORAT PROVINSI KALIMANTAN TIMUR - Asnah Wahyuni (ADMINISTRASI PUBLIK, 2018)
This study aims to describe the condition of the capability of East Kalimantan Province Inspectorate, the constraints faced in increasing its capability and the efforts made by Inspectorate of East Kalimantan Province to increase its capability based on internal audit capability model (IACM). This research use desciptive qualitative approach. The scope of the discussion is in East Kalimantan Province Inspectorate. The data used are the primary data obtained from interviews, questionnaires, observations, and documentation studies, as well as secondary data in the form of documents related to the research. The focus of the research is the capability of the Government Internal Supervisory Apparatus using the internal audit capability model with six indicators, namely Roles and Services, Human Resource Management, Professionalism Practices, Management and Performance Accountability, Organizational Relations and Culture and Governance Structure. The results show the level of capability of Inspectorate of East Kalimantan Province at level 3 with note (there are still elements that must be upgraded by APIP to go to full level), that is the East Kalimantan Provincial Inspectorate must arrange the plan to reach Level 3 on 4 elements as role element and Service , HR Management, Professionalism Practice and Governance Structure. To overcome the matters in these elements, East Kalimantan Provincial Inspectorate performs capability improvement efforts in accordance with the complete capabilities of APIP Under the Regulation of the Head of BPKP Number 1633 / K / JF / 2011 to realize an effective role for clear in Government regulations Number 60 /2008.